Tradeoffs between beach nourishment and managed retreat: Insights from dynamic programming for climate adaptation decisions. (March 2020) - Cutler, Emma M.; Albert, Mary R.; White, Kathleen D.
Abstract: Coastlines are vulnerable to sea level rise, erosion, and flooding, all predicted to worsen as climate change continues. Models are needed that incorporate dynamic processes within coupled economic and physical systems for decision-makers, including when to retreat from hazardous areas. This paper presents a coupled geo-economic model of beach width and property value with exogenous sea level rise. Discrete dynamic programming identifies optimal beach nourishment and managed retreat strategies. As a new contribution, we treat expected damages as costs, which demonstrates that increased damage offsets some benefits of development along hazardous coastlines. The model identifies managed retreat as preferable to beach nourishment when damages exceed a threshold. Regret associated with retreat depends on sea level rise damages and the timeframe of analysis. Considering dynamic complexity of coastal systems, as this model does, may produce climate adaptation plans that better address community needs and reduce risk over timescales of interest. Graphical abstract: Image 1 Highlights: Treating damages as costs removes perverse incentives to develop hazardous coasts. Relocation becomes optimal when the proportion of value damaged exceeds a threshold. Optimal decisions are sensitive to the value of vulnerable assets. Waiting too long to retreat could be more costly than retreating too soon.